Incomplete Information, High-Low Bidding and Public Information in First Price Auctions - Lee, Tom K. (Management Science, 1984)
High-low bidding refers to auctions of a series of objects where for a subset of the auctioned objects one of two buyers bids high on some objects and low on others while the other buyer does the reverse. This paper shows that high-low bidding does not imply collusive behavior among buyers. In particular, through a formal modeling of a noncooperative game of information acquisition and bidding decisions, it shows that high-low bidding can be obtained. The paper also demonstrates that if the cost of information to a seller is less than the equilibrium joint expected information cost of the buyers, then it pays the seller to provide public information. Finally, if the provision of public information is not feasible but a seller can know whether buyers have acquired information, then it pays the seller to make known to the buyers and to pursue a policy that just prior to the start of an auction the seller will announce which buyer has acquired information.